Análisis de confiabilidad de un alimentador de la Empresa Eléctrica Riobamba S.A. - Taday Álvarez, Cesar Augusto (2022)
In the present research work, it was decided to analyze the repowering, reconfiguration and automatic load transfer alternatives in the 1500130T03 feeder, considering the study from the head of the Alao distribution substation, using the CYMDIST software, through which the to determine the failure rate, repair, availability and unavailability. As a starting point in the present study, the type and duration of failures is chosen. In the "Reliability Analysis" module of the CYMDIST software, the reliability indexes referred to the consumer are obtained, results that allow to identify a reconfiguration and optimal route in a prudent analysis time, the repair time must be less than the maneuver time for a reconnection, in addition, the conditions that the feeders involved in the load transfer must meet were determined, since they must guarantee an adequate operation before and after, the location of the automatic reconnection equipment with its communication was also defined. Finally, the referential budget was analyzed when making the respective changes and incorporation of this equipment to the 1500130T03 feeder of the Alao substation of Empresa Eléctrica Riobamba S.A.